Heteroleptic samarium(iii) halide complexes probed by fluorescence-detected L3-edge X-ray absorption spectroscopy. Issue 31 (23rd May 2018) - Goodwin, Conrad A. P.; Réant, Benjamin L. L.; Kragskow, Jon G. C.; DiMucci, Ida M.; Lancaster, Kyle M.; Mills, David P.; Sproules, Stephen
Abstract : The novel series of heteroleptic Sm(iii ) halide complexes provides the backdrop for a fluorescence-detected Lα1 X-ray absorption spectroscopic study. Abstract : The addition of various oxidants to the near-linear Sm(ii ) complex [Sm(N †† )2 ] (1 ), where N †† is the bulky bis(triisopropylsilyl)amide ligand {N(Si i Pr3 )2 }, afforded a family of heteroleptic three-coordinate Sm(iii ) halide complexes, [Sm(N †† )2 (X)] (X = F, 2-F ; Cl, 2-Cl ; Br, 2-Br ; I, 2-I ). In addition, the trinuclear cluster [{Sm(N †† )}3 (μ2 -I)3 (μ3 -I)2 ] (3 ), which formally contains one Sm(ii ) and two Sm(iii ) centres, was isolated during the synthesis of2-I . Complexes2-X are remarkably stable towards ligand redistribution, which is often a facile process for heteroleptic complexes of smaller monodentate ligands in lanthanide chemistry, including the related bis(trimethylsilyl)amide {N(SiMe3 )2 } (N′′). Complexes2-X and3 have been characterised by single crystal X-ray diffraction, elemental analysis, multinuclear NMR, FTIR and electronic spectroscopy. The Lα1 fluorescence-detected X-ray absorption spectra recorded at the Sm L3 -edge for2-X exhibited a resolved pre-edge peak defined as an envelope of quadrupole-allowed 2p → 4f transitions. The X-ray absorption spectral features were successfully reproduced using time-dependent density functional theoretical (TD-DFT) calculations that synergistically support the experimental observations as well as the theoretical model upon which the electronic structure and bonding in these lanthanide complexes is derived.